2007
DOI: 10.2139/ssrn.988305
|View full text |Cite
|
Sign up to set email alerts
|

The Free Trade Agreement between the United States and Morocco: The Importance of a Gradual and Assymetric Agreement

Abstract: Abstract:The agreement recently signed between Morocco and the United States foresees several modalities in dismantling tariffs. Our simulations show that the various modalities of trade liberalization may have different impacts on the welfare, the rate of growth and the sectoral trade balance of these two countries. More precisely, our findings justify the interest of a gradual and asymmetrical agreement. In addition, the FTA between the US and Morocco will have a significant impact not only on trade between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
(4 reference statements)
1
2
0
Order By: Relevance
“…This would be welfare improving for South Africa because consumers of the imports whose prices fall would enjoy the goods at a lower cost. These findings are in line with the research of (Abdelmalki et al 2007) on the impact of FTA between the US and Morocco. In this case, the agreement led to a total welfare gain by Moroccan consumers because they had access to goods at lower prices.…”
Section: Trade Creation and Trade Diversionsupporting
confidence: 92%
See 1 more Smart Citation
“…This would be welfare improving for South Africa because consumers of the imports whose prices fall would enjoy the goods at a lower cost. These findings are in line with the research of (Abdelmalki et al 2007) on the impact of FTA between the US and Morocco. In this case, the agreement led to a total welfare gain by Moroccan consumers because they had access to goods at lower prices.…”
Section: Trade Creation and Trade Diversionsupporting
confidence: 92%
“…Another study in the United States by Abdelmalki, Sandretto and Jallab (2007) assesses the FTA between the US and Morocco using the WITS-SMART Simulation Model. The findings showed that the FTA significantly reduced Moroccan tariff by more than US$ 147 million.…”
Section: Empirical Literaturementioning
confidence: 99%
“…As the focus of this study is based on a single market (South Africa), the application of the SMART PE model framework to this study is relevant. The research study emulates the methodology applied byAbdelkmalki, Jallab and Sandretto (2007), who applied the SMART PE model to explore the implications of trade liberalisation between the United States and Morocco.It is generally accepted that when import tariffs are abolished in post-AfCFTA negotiations, commodity prices will fall, leading to trade creation. Trade creation involves stimulating trade levels after the tariff liberalisation, leading to unproductive companies being outcompeted by more productive rivals Laird and Yeats (1986).…”
mentioning
confidence: 99%